2018
DOI: 10.1021/acs.cgd.8b00815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structures, and Solid-State Polymerization of 8-[4-(Dimethylamino)phenyl]octa-5,7-diynyl Carbamates

Abstract: Six butadiyne monomers with (dimethylamino)­phenyl and N-substituted urethane substituents were synthesized and their crystal structures and solid-state polymerization were investigated. In five of the six monomers, directions of the butadiyne stacking and the intermolecular hydrogen bonding between urethane groups coincided, and translational distance d between adjacent butadiyne moieties was around 5 Å. Among them, four monomers showed angle θ between the translation axis of the monomers and the butadiyne mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The design and synthesis of novel organic polymers through topochemical reactions, such as [2 + 2], [4 + 4], [4 + 2], and [1,4]-addition are of recent interest owing to ease of synthesis with deducible and tunable structural features in high yields and also due to the day-to-day applicative aspects of the organic polymers. In particular, the synthesis of crystalline 1D and 2D organic polymers containing cyclobutanes in the backbone through [2 + 2] reactions of diene and trienes, respectively, are of immense interest given their uniqueness and difficulty in finding such monomers with requisite crystal structures. Integrating such monomers of dienes into the network of coordination polymers was shown to promote [2 + 2] polymerization reactions to produce coordination polymers of organic polymers (CPOPs) in single crystal to single crystal transformations upon irradiation. …”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of novel organic polymers through topochemical reactions, such as [2 + 2], [4 + 4], [4 + 2], and [1,4]-addition are of recent interest owing to ease of synthesis with deducible and tunable structural features in high yields and also due to the day-to-day applicative aspects of the organic polymers. In particular, the synthesis of crystalline 1D and 2D organic polymers containing cyclobutanes in the backbone through [2 + 2] reactions of diene and trienes, respectively, are of immense interest given their uniqueness and difficulty in finding such monomers with requisite crystal structures. Integrating such monomers of dienes into the network of coordination polymers was shown to promote [2 + 2] polymerization reactions to produce coordination polymers of organic polymers (CPOPs) in single crystal to single crystal transformations upon irradiation. …”
Section: Introductionmentioning
confidence: 99%
“…Polydiacetylene (PDA) is a class of mechanochromic polymers, including nonamphiphilic and amphiphilic ones with hydrophobic (e.g., alkyl, aryl) chains on one end, and a hydrophilic headgroup (e.g., −COOH, −NH 2 , −ester) or other moieties (e.g., aryl, , etoxisilane, urethane, or isocyanate groups) on the other end, that was initially reported in the late 1960s . It is known to change color and become fluorescent when it is exposed to heat, pH variation, adsorption of ions, and other molecules. , Over the years, its monomer assembly, polymerization process, polymer structure, and mechanochromic properties have been characterized based on measurements via the Langmuir–Blodgett technique, electron paramagnetic resonance (EPR), X-ray crystallography, UV–vis, fluorescence, infrared (IR), Raman spectroscopy, nuclear magnetic resonance (NMR), scanning tunneling microscopy (STM), atomic force microscopy (AFM), fluorescence microscopy, and electrical conductivity .…”
mentioning
confidence: 99%
“…In this case, the polymerization scheme seems to be not as regular as for the compounds of type I. Actually, in our previous study, we confirmed by single-crystal X-ray crystallographic analysis that the butadiyne derivatives showing the polymer absorption of type II aligned under the conditions with a large deviation from d = 0.5 nm and θ = 45° in Figure …”
Section: Resultsmentioning
confidence: 66%
“…Actually, in our previous study, we confirmed by singlecrystal X-ray crystallographic analysis that the butadiyne derivatives showing the polymer absorption of type II aligned under the conditions with a large deviation from d = 0.5 nm and θ = 45°in Figure 1. 52 Powder X-ray diffraction patterns of the monomers were obtained as shown in Figure 4. Sharp diffraction peaks were observed for the compounds with phenyl or trimethoxyphenyl groups: i.e., H-0, H-1, C 1 O-0, and C 1 O-1.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation